2017
DOI: 10.1016/j.brainres.2017.03.003
|View full text |Cite
|
Sign up to set email alerts
|

The effects of CRF and urocortins on the sociability of mice

Abstract: The aim of our study was to determine the role of corticotropin-releasing factor (CRF), the urocortins (Ucn1, Ucn2 and Ucn3) and their receptors (CRF and CRF) in the sociability of mice. Male CFLP mice were administered intracerebroventricularly (icv) with CRF and urocortins alone or in combination with antalarmin (specific CRF antagonist) and astressin (specific CRF antagonist) and then investigated in a Crawley social interaction test arena, that consists of three chambers. An unknown male in a cage was put … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(23 citation statements)
references
References 47 publications
0
23
0
Order By: Relevance
“…Accordingly, the CRF 1 receptor-preferring antagonist antalarmin did not affect sociability in substance-naive male mice, as assessed in the three-chamber task (Bagosi et al, 2017). In contrast, other studies reported increased non-aggressive olfactory investigation in male Syrian hamsters treated with the CRF 1 receptor-preferring antagonist SSR125543A, as assessed in a resident-intruder paradigm for aggressive behavior (Farrokhi et al, 2004).…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…Accordingly, the CRF 1 receptor-preferring antagonist antalarmin did not affect sociability in substance-naive male mice, as assessed in the three-chamber task (Bagosi et al, 2017). In contrast, other studies reported increased non-aggressive olfactory investigation in male Syrian hamsters treated with the CRF 1 receptor-preferring antagonist SSR125543A, as assessed in a resident-intruder paradigm for aggressive behavior (Farrokhi et al, 2004).…”
Section: Discussionmentioning
confidence: 74%
“…For instance, intracerebroventricular administration of CRF increased partner preference in male prairie voles but decreased interest for an unfamiliar conspecific in mice (Bagosi et al, 2017;DeVries, Guptaa, Cardillo, Cho, & Carter, 2002). Moreover, transgenic CRF overexpression, CRF 2 receptor-or urocortin 3-deficiency increased time-dependent social discrimination in mice (Deussing et al, 2010;Kasahara et al, 2011).…”
mentioning
confidence: 99%
“…Despite our findings that activation of Corticotropin-Releasing Factor (CRF)-expressing neurons contained within the oval nucleus of the Bed Nucleus of the Stria Terminalis (BNSTov) produces pro-resilient behavioral responses, several studies have reported that this activation induces negative emotional states. [3][4][5][6][7][8] Previously, we show that BNSTov CRF activation had a pro-social effect only after cumulative stress exposure 1 , suggesting a role for BNSTov CRF neurons in potentially promoting cooperative sociality under stressful conditions. This adaptive function confers an evolutionary advantage.…”
Section: Resultsmentioning
confidence: 81%
“…In the sociability and preference for social novelty test, a three-chamber social interaction box (L × W × H: 60 × 20 × 25 cm) was used [ 74 ]. First, the tested male animal was familiarized with the middle chamber for 5 min; then, the male was allowed to explore the adjacent chambers for another 5 min [ 71 , 72 ]. In this paradigm, two types of tests can be performed [ 71 , 72 ].…”
Section: Experiments In Micementioning
confidence: 99%
“…First, the tested male animal was familiarized with the middle chamber for 5 min; then, the male was allowed to explore the adjacent chambers for another 5 min [ 71 , 72 ]. In this paradigm, two types of tests can be performed [ 71 , 72 ]. The first test was used to investigate the sociability of animals; in this test, the male can choose between a stranger male conspecific set in a cage and an empty cage [ 71 , 72 ].…”
Section: Experiments In Micementioning
confidence: 99%